Budgeting and reporting for public-private partnerships - Katja Funke; Tim Irwin; Isabel Rial (Organisation for Economic Co-operation and Development (OECD), International Transport Forum, 2013)
Public-private partnerships (PPPs) can appeal to governments because they offer a new way of providing public services that is possibly more efficient than traditional public finance. But they can also appeal to governments because they allow new investments to be undertaken without any immediate increase in reported government spending or debt. This second motive for using PPPs rests largely on an illusion, because in the absence of efficiency gains (which are probably small relative to the total cost of the project), PPPs and publicly financed projects have a similar long-run effect on public finances. In some PPPs, the government defers payment, but ultimately must still pay the full cost of the project. In others, it concedes the right to collect user fees, and thus loses revenue it would have collected if the project had been financed traditionally.
Keywords: 330; Öffentlich-private Partnerschaft; Öffentliche Finanzen